OPTIMALISASI CASHFLOW MENGGUNAKAN METODE PENJADWALAN EST DAN PENGATURAN SUMBERDAYA PADA PROYEK BANGUNAN GEDUNG - Riskijah, Sitti Safiatus (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2014)
An appropriate and accurate management of financial source will be able to run activities of a project well and increases the contractor?s profit. This reasearch aims at determining the kind of optimum cashflow of a multi purpose construction project in Malang. Schedule, debits and credits, loan interest, installment plan, completed with the system of contract payment from the owner to the contractor were needed to make the cash flow. It was done by employing 20% and 0% down payment based on EST (Earlierst Start Time), 27 kinds of resource payment system varied in start, prorate, and end of cost, material, and work. Each Cash flow will not only determine the balance of payments and total credits of each period but also the profit. The findings the show that the kinds of Cash flow which gives maximum profit for contractors, are as follow: 1) the one based on EST with no down payment system at a difference profit of IDR 109.708.207,51 or 1,5%; 2) the one based on arrangement of cost, material, and work payment system which results in Start-End-End payment; 3) the application of the two Cash flow systems results in? Start-End-End system is able to give maximum profit of IDR 7.869.632.694,74.Keywords: Cash flow, debit, credit, payment system, maximum profit